O texto museológico e a sua tradução - Tryhub, Anastasiya (2022)
This report was produced as part of the Master’s Degree in Specialized Translation and Interpreting and aims to describe, analyze and reflect on the work carried out during the curricular internship at the Portuguese Center of Photography. This work consisted in translating different museological contents from Portuguese into English, from photographic camera exhibitions to technical texts in the field. The first part of the report deals with the theory that serves as the basis for the second part, in which the translation work carried out during the internship is presented together with its in-depth analysis, highlighting the translation difficulties and the solutions and translation processes found to overcome them. The focus of this report is mainly on technical translation related to photography and cameras, as well as text production for modern museums. It aims to answer questions such as: What are the characteristics and typologies of a museological discourse? What distinguishes it from other texts? What challenges does it pose to a translator? Why is competent and deliberate text production and translation so important in a modern museum? Issues such as the importance of terminology for a technical translation, translation into a non-native language and the problems arising from the lack of standardization of technical vocabulary will also be addressed.